(untitled) - Johnson, Palmer O. (New Jersey, 1949)
Contents: Chapter 1: The realm of statistics; Chapter 2: Probability and Likelihood; Chapter 3: Sampling Distributions; Chapter 4: The testing of statistical hypotheses; Chapter 5: Current Procedures in testing statistical hypotheseses, ...
Keywords: Statistics,Thống kê